Development of an Automatic Presence Online Training Model Based on IMPE (Interaction, Material, Project, Evaluation) in the Merdeka Belajar Era - Khairul Arifin; Yuli Kurniawati Sugiyo Pranoto; Farid Ahmadi (Universitas Negeri Semarang, 2023)
Efforts to improve the quality of education include various pieces of training to improve teacher competence, for example by facilitating classroom administration. Therefore, schools must pay attention to teacher performance with all the effort and capital to improve these skills. This study aims to develop an automatic presence online training model and also look at increasing teacher competency in class administration automation. The research method used is the development method with the ADDIE model. The object of research is participants in automatic presence training, the majority of whom are teachers, research instruments are in the form of questionnaires, questionnaires, and interviews. Regression is used as a method of analysis. The results showed that based on the results of calculations on the Wilcoxon Signed Rank Test, Asymp. Sig is 0.021 which means <0.05. Then the results of the post-test > pre-test. So that it can be said that the IMPE model has proven to be effective in increasing the competence of participants in automated attendance online training. These findings confirm that the IMPE-based training model can increase teacher competency in class administration automation.